THE INFLUENCE OF EXTRINSIC MOTIVATION ON INTEREST IN VISITING THE LE HU GARDEN TOURISM OBJECT - Rianto Manurung (Jurnal Ekonomi, 2022)
Tourism is starting to rise again and compete from its residency so far due to the Covid-19 outbreak that has hit the world. Along with the leniency in wearing masks in open places set by the government, tourism activists began competing to provide complete facilities and unique attractions with the aim of attracting visitors to be interested in coming to their tourist attraction locations. The Le Hu Garden is one of the tourist sites in Medan, precisely in Deli Serdang which offers facilitiesand complete health protocols accompanied by the attraction of a unique flower garden. Visitors who come are also very happy with the facilities and flower gardens as an attraction to come and invite their families. The results show that the facilities provided greatly affect the interest of the visitors to come. The attraction presented by The Le Hu Garden is in the form of a unique flower garden display that attracts visitors. Simultaneously, facilities and attractions have a positive effect on interest in visiting.This research usesusing three variables, namelytwo independent variables, and one dependent variable, where facilities (X1), tourist attraction (X2) are independent variables, while visiting interest (Y) is the dependent variable. The tests used in this research are the reliability test, normality test, multicollinearity test, heteroscedasticity test, coefficient of determination (R2), test (t), test (F)